2015
DOI: 10.1097/mao.0000000000000813
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Computer-Controlled and Modified Roll Maneuver for Treatment of Geotropic Lateral Canal Benign Paroxysmal Positional Vertigo

Abstract: The CMRM consisting of three sequential 360-degree rotations for geotropic lateral canal BPPV has a higher initial success rate compared with the conventional RM consisting of one 360-degree rotation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
(40 reference statements)
1
5
0
Order By: Relevance
“…Although the direction of rotation is different in cervical vertigo, there were no differences for the ipsilateral vertebral artery diameter between the two groups, as well as between the groups before operation and after operation. This result was consistent with previous studies 14,15 that showed there was no correlation between the severity of cervical vertigo and the direction of neck rotation.…”
Section: Discussionsupporting
confidence: 83%
“…Although the direction of rotation is different in cervical vertigo, there were no differences for the ipsilateral vertebral artery diameter between the two groups, as well as between the groups before operation and after operation. This result was consistent with previous studies 14,15 that showed there was no correlation between the severity of cervical vertigo and the direction of neck rotation.…”
Section: Discussionsupporting
confidence: 83%
“…Biaxial chairs facilitate the consistency of speed, angle, and amplitude of the diagnostic maneuvers. 41,42 Another study by Shan et al 4 found that treatment for geotropic HC-BPPV with rotation at 120 /s succeeded by two slower rotations had a higher success rate compared to conventional barbecue. The study did not have a control group and bias of being treated in a biaxial chair compared to conventional treatment was not corrected for.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of acceleration and deceleration during barbecue maneuvers for horizontal canal benign paroxysmal positional vertigo (HC-BPPV) has been debated. [1][2][3][4] is the most common cause of vertigo, and HC-BPPV is the second most common subtype, 5,6 with a prevalence ranging from 5% to 30% in patients with BPPV. [7][8][9] The commonly accepted cause of BPPV is ectopic otoconia located within the lumen of the semicircular canals (canalolithiasis) or attached to the cupula (cupulolithiasis), 10,11 generating attacks of positional nystagmus and vertigo after certain head movements.…”
Section: Introductionmentioning
confidence: 99%
“…The right horizontal canal BPPV was diagnosed, suggesting this was due to canal conversion from the posterior canal to the horizontal canal after the initial Epley maneuver. 2,10 Then, the patient was treated with a device-assisted and modified Lempert maneuver as described elsewhere, 11 and 5 days later, the patient received a repeated maneuver due to his remaining vertigo and persistent positive for the roll test. After this, the patient's symptoms resolved completely, with negative results in subsequent diagnostic tests.…”
Section: Casementioning
confidence: 99%
“…2,8 Some devices have been developed to treat BPPV with promising treatment outcomes. [8][9][10][11][12] We present herein two rare cases of BPPV secondary to laparoscopic surgery and the two patients were treated successfully with manual or device-assisted repositioning maneuvers.…”
Section: Introductionmentioning
confidence: 99%